Ochratoxin A: 50 Years of Research - Malir, Frantisek; Ostry, Vladimir; Pfohl-Leszkowicz, Annie; Malir, Jan; Toman, Jakub (Toxins, 2016)
Since ochratoxin A (OTA) was discovered, it has been ubiquitous as a natural contaminant of moldy food and feed. The multiple toxic effects of OTA are a real threat for human beings and animal health. For example, OTA can cause porcine nephropathy but can also damage poultries. Humans exposed to OTA can develop (notably by inhalation in the development of acute renal failure within 24 h) a range of chronic disorders such as upper urothelial carcinoma. OTA plays the main role in the pathogenesis of some renal diseases including Balkan endemic nephropathy, kidney tumors occurring in certain endemic regions of the Balkan Peninsula, and chronic interstitial nephropathy occurring in Northern African countries and likely in other parts of the world. OTA leads to DNA adduct formation, which is known for its genotoxicity and carcinogenicity. The present article discusses how renal carcinogenicity and nephrotoxicity cause both oxidative stress and direct genotoxicity. Careful analyses of the data show that OTA carcinogenic effects are due to combined direct and indirect mechanisms (e.g., genotoxicity, oxidative stress, epigenetic factors). Altogether this provides strong evidence that OTA carcinogenicity can also occur in humans.
Keywords: ochratoxin A; microfungi; DNA Damage; toxikologie; epigeneze genetická; potravinářská mikrobiologie; History, 20th Century; dějiny 20. století; lidé; regulace genové exprese u nádorů; Epigenesis, Genetic; Food Microbiology; Toxicology; poškození DNA; Risk Assessment; Balkan Nephropathy; toxicity; Oxidative Stress; balkánská nefropatie; carcinogenicity; Kidney Neoplasms; food; hodnocení rizik; zvířata; Humans; Gene Expression Regulation, Neoplastic; urothelial cancer; ledviny; feed; Balkan endemic nephropathy; rizikové faktory; nádorová transformace buněk; Kidney; oxidační stres; dějiny 21. století; ochratoxiny; Risk Factors; biomarkers; Cell Transformation, Neoplastic; nádory ledvin; History, 21st Century; Ochratoxins; Animals